Community-based recovery and youth justice - Sellers, Brian G. (Criminal justice and behavior, 2015)
Four well-known delinquency intervention and prevention programs remain both publicly and politically popular regardless of a large body of evidence-based research revealing their ineffectiveness in promoting a lasting desistance from youth violence and crime. Scared straight programs, Drug Abuse Resistance Education (D.A.R.E.), youth boot camps, and secure large-scale, custodial juvenile correctional facilities overemphasize offender ?risk management and maintenance? as opposed to individual, group-based, and/or collective well-being. This article will identify the values that these current and dominant community-centered youth justice initiatives reflect, and it will explain how these values further (or forestall) offender desistance. Viable, evidence-based alternatives consistent with the value orientation of therapeutic and restorative programming will also be evaluated. The article concludes by examining the efficacy of this alternative normative agenda to foster successful desistance from juvenile delinquency and crime.